(untitled) (Journal of the College of Basic Education, 2022)
The poetic characteristic of women is evidence of her presence in the arena of Arabic poetry, and her artistic ability to say poetry. God granted it to individuals of His servants.Poetry is a world rich in images that are undulating with movement through the word, symbol and rhythm, and it in turn relies on the imagination in the semantics of words and charging them with new meanings and impressive and eloquent revelations that aim to discover new relationships that are perceived by feeling and feeling.